Body mass index trajectories across adulthood and smoking in relation to prostate cancer risks: the NIH-AARP Diet and Health Study. (29th October 2018) - Kelly, Scott P; Lennon, Hannah; Sperrin, Matthew; Matthews, Charles; Freedman, Neal D; Albanes, Demetrius; Leitzmann, Michael F; Renehan, Andrew G; Cook, Michael B
Abstract: Background: Previously we showed that adulthood body mass index (BMI) trajectories that result in obesity were associated with elevated risks of fatal prostate cancer (PCA). To further explore this relationship, we conducted a study within the NIH-AARP Diet and Health Study. Methods: Among 153 730 eligible men enrolled in the NIH-AARP cohort from 1995 to 1996 (median follow-up = 15.1 years), we identified 630 fatal PCA cases and 16 896 incident cases. BMI was assessed for ages 18, 35 and 50 and at study entry, enabling examination of latent class-identified BMI trajectories. Hazard ratios (HRs) and 95% confidence intervals (CI) were estimated using Cox proportional hazards regression. Results: BMI at study entry (mean age = 63, HR = 1.12; 95% CI = 1.01, 1.24, per 5-unit increase) and maximum BMI during adulthood (HR = 1.12; 95% CI = 1.02, 1.24, per 5-unit increase) shared modest associations with increased risk of fatal PCA. Smoking status likely modified the relationship between BMI trajectories and fatal PCA ( Pinteraction = 0.035 via change-in-estimate variable section, P = 0.065 via full a priori model). Among never-smokers, BMI trajectory of normal weight to obesity was associated with increased risk of fatal disease (HR = 2.37; 95% CI = 1.38, 4.09), compared with the maintained normal weight trajectory, whereas there was no association among former or current-smokers. Total and non-aggressive PCA exhibited modest inverse associations with BMI at all ages, whereas no association was observed for aggressive PCA. Conclusions: Increased BMI was positively associated with fatal PCA, especially among never-smokers. Future studies that examine PCA survival will provide additional insight as to whether these associations are the result of biology or confounding.